The role of physical activity and unhealthy diet on ADHD symptoms and emotional well-being in adolescents diagnosed with ADHD - Lára Borg Bolladóttir 1993- (2016)
Studies have indicated that healthier dietary pattern and physical activity can improve mental health in the general population. However, limited amount of researches have examined these non-pharmacological interventions on ADHD symptoms and emotional well-being among adolescents diagnosed with ADHD. The aim of this study was to examine this relationship among 13-16 years old adolescents diagnosed with ADHD. The data used in this study came from the 2014 annual population-based, Youth in Iceland, survey. ADHD symptoms were assessed using 18-items self-reported questionnaire of statements related to ADHD symptoms. Emotional well-being was assessed using 10 depression items and four anxiety items from the SCL-90. Results revealed that male had more ADHD symptoms than female. Students low on unhealthy diets showed fewer ADHD symptoms than those high on unhealthy diet. There was no difference on ADHD symptoms after level of physical activity. Students low on unhealthy diet showed more positive emotional well-being than those high on unhealthy diet. Students high on physical activity showed more positive emotional well-being than those who engaged in low or moderated physical activity. Female showed more negative symptoms of emotional well-being than males. Keywords: ADHD, physical activity, depression, anxiety, unhealthy diet Rannsóknir hafa sýnt fram á að heilsusamlegt mataræði og hreyfing getur bætt andlega heilsu hjá almenningi. Hinsvegar hafa rannsóknir verið takmarkaðar varðandi tengsl á ADHD einkennum og tilfinningalegri líðan meðal unglinga sem greinast með ADHD. Markmið þessarar rannsóknar var að kanna þetta samband meðal unglinga, á aldrinum 13-16 ára, sem greindir voru með ADHD. Í rannsókninni voru notuð gögn úr Ungt fólk 2014. ADHD einkenni voru metin með 18 atriða spurningalista. Andleg vellíðan var metin með 10 atriða spurningalista varðandi þunglyndi og fjögurra atriða spurnigalista varðandi kvíða þar sem notast var við SCL-90. Niðurstöður leiddu í ljós að karlar höfðu fleiri ADHD einkenni en konur. ...